The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10646-015-1602-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of Headline® fungicide to Blanchard’s cricket frogs (Acris blanchardi)

Abstract: Previous laboratory studies have suggested that pyraclostrobin-containing fungicide formulations are toxic to amphibians at environmentally relevant concentrations. However, it is unknown if all pyraclostrobin formulations have similar toxicity and if toxicity occurs in different amphibian species. We investigated the acute toxicity of two formulations, Headline(®) fungicide and Headline AMP(®) fungicide, to Blanchard's cricket frogs (Acris blanchardi) based on a direct overspray scenario. In addition, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Also, pesticide applications were the most frequent management measures in viniculture (up to 12 applications) and can affect amphibians not only on the application day, like tillage operations, but up to several days after application, depending on the chemical decomposition of pesticides. Recent studies and surveys confirmed the presence of pesticides in amphibian habitats and waterbodies in general (Smalling et al, 2012; Ulrich et al, 2015), as well as in amphibian tissues (Smalling et al, 2013; Smalling et al, 2015; Battaglin et al, 2016; Cusaac et al, 2016). Furthermore, pesticide concentrations in amphibian tissues were positively correlated with agricultural and urban land around breeding sites (Battaglin et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Also, pesticide applications were the most frequent management measures in viniculture (up to 12 applications) and can affect amphibians not only on the application day, like tillage operations, but up to several days after application, depending on the chemical decomposition of pesticides. Recent studies and surveys confirmed the presence of pesticides in amphibian habitats and waterbodies in general (Smalling et al, 2012; Ulrich et al, 2015), as well as in amphibian tissues (Smalling et al, 2013; Smalling et al, 2015; Battaglin et al, 2016; Cusaac et al, 2016). Furthermore, pesticide concentrations in amphibian tissues were positively correlated with agricultural and urban land around breeding sites (Battaglin et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Pesticides play a crucial role in this context, since they can be highly toxic to terrestrial life stages of amphibians (Brühl et al, 2013; Cusaac et al, 2016). Additionally, a spatio-temporal overlap of pesticide applications with the terrestrial activity phase of amphibians was demonstrated for some crops (Lenhardt, Brühl & Berger, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In most experiments, exposure containers consisted of 9.5‐L aquaria (∼400 cm 2 floor surface area) containing moist soil to 1 cm depth uniformly distributed across the bottom of the aquarium. Unless otherwise noted, the standard bedding soil described in Cusaac et al was used in exposure containers. Treatment rates were determined based on maximum label rates for each fungicide formulation (152 and 217 g pyraclostrobin/ha for Headline AMP and Headline fungicides, respectively, corresponding to 1.52 and 2.17 μg pyraclostrobin/cm 2 , respectively), and formulations were mixed with deionized water to achieve nominal treatment rates.…”
Section: Methodsmentioning
confidence: 99%
“…Crickets fed to juvenile toads in experiment 4 were analyzed for fungicide active ingredients using a modification of the QuEChERS method , as described in Cusaac et al . Briefly, 10 crickets from each treatment were placed in 50‐mL centrifuge tubes ( n = 19 and 21 tubes in control and Headline AMP treatments, respectively) after treatment and frozen at –20 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation